A Pedometer-based Intervention with Daily Walking Steps and its Relationship with Nutritional Status among Overweight/Obese University Students in Kuala Terengganu - J.L, Kok; A., Asma’; K, Khairil-Shazmin; M.Y, Hayati (IIUM Medical Journal Malaysia, 2018)
Introduction: The aim of this study was to determine the effects of pedometer-based intervention and the relationship between daily walking steps and nutritional status among overweight/obese university students in Kuala Terengganu. Materials and methods: The study was an 8-week intervention study that included 23 overweight/obese university students. After 7 days of baseline activity, anthropometric data such as weight, height and waist circumference and a one-day dietary record were taken. The participants were divided into a control and case group. The control group (n=15) was instructed to continue with their normal activities and habits throughout the 8 weeks. The case group (n=8) was instructed to walk based on the targeted number of steps. Data such as body weight, waist circumference and a one-day dietary record were taken after the intervention. Results: Both case and control group show significant differences in body mass index (BMI) with p=0.017 and p=0.047 respectively. However, there is a large and significant difference between walking steps and BMI before and after intervention for the case group. There were no differences in any other study parameters during the 8-week study. Conclusion: In conclusion, short-term intervention with a pedometer increased physical activity and positively affected the BMI of overweight/obese participants. The use of a pedometer was efficient in measuring daily physical activity (r= 0.756, p< 0.05).